ChemInform Abstract: Carbon—Carbon Bond Cleavage for Cu‐Mediated Aromatic Trifluoromethylations and Pentafluoroethylations. Issue 12 (March 2016) - Sugiishi, Tsuyuka; Amii, Hideki; Aikawa, Kohsuke; Mikami, Koichi
Abstract: Review: [54 refs.